Estimasi Daya Keluaran Fotovoltaik Menggunakan Algortima Genetik - Bago, Sri Intan; Irwanto, Muhammad (LPPM UNIKA Santo Thomas Medan, 2025)
The development of renewable energy systems is a major focus in efforts to reduce environmental impacts and dependence on fossil energy sources. One promising renewable energy source is solar energy, which can be utilized through photovoltaic technology. However, to increase the efficiency of the photovoltaic system, an accurate estimate of the output power produced is required. This study aims to develop a photovoltaic output power estimation model using MATLAB-based Genetic Algorithm (GA). Genetic Algorithm was chosen because of its ability to find optimal solutions to a problem using the principles of natural selection. In this study, parameters that affect the performance of the photovoltaic system, such as sunlight intensity, cell temperature, and panel tilt angle, will be analyzed and modeled. The results of this photovoltaic output power estimation model are expected to provide more accurate predictions, so that they can be used for decision making in the planning and development of solar energy systems. Through simulation and data analysis, this study is expected to make a significant contribution to the development of photovoltaic technology in Indonesia and increase the efficiency of its use. Keyword : Photovoltaik, Output power, Genetic Algorithm, MATLAB, Renewable Energy